Seaweed and the applicability of freeze drying techniques - Ashworth, Helen; Donohoe, Paul; Kibblewhite, Blair (Frontiers in Marine Science, 2024)
Seaweed, often considered an overlooked resource, are marine algae with many applications in various industries. The many species of seaweed possess a range of nutritional values, environmental benefits, and their versatility make them an attractive subject of research and development. One promising method for preserving and utilising seaweed effectively is freeze drying. This review explores the world of seaweed, its properties, applications, and the potential of freeze-drying techniques in harnessing the above benefits. The review examines the freeze-drying process and discusses its applicability and advantages in preserving seaweed as a sustainable resource. The discussion also includes the diverse uses of seaweed, from culinary applications to pharmaceuticals and beyond, highlighting the potential of freeze-drying to unlock seaweed’s full potential